Modification of Fourth order Runge-Kutta Method for Kutta Form With Geometric Means - Suryani, Irma; Roni, Roni; Wartono, Wartono; Muda, Yuslenita (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2020)
This paper Â discuss how to modified Fourth order Runge-Kutta Kutta method based on the geometric mean. Then we have parameters Â andÂ Â however by re-comparing the Taylor series expansion ofÂ Â and Â up to the 4th order.Â For make error term re-compering ofÂ the Taylor series expansion ofÂ and Â up to the 5th order. In the error term an make substitution for the values ofÂ and Â into the Taylor seriese expansion up to the 5th order. So that we have error term modified Fourth Order Runge-Kutta Kutta based on the geometric mean.Â Modified Fourth Order Runge-Kutta Kutta based on the geometric mean that usually used to solved ordinary differential equations.